Transgenerational Effects of Prenatal Ethanol Exposure in Prepubescent Mice - Bottom, Riley T.; Kozanian, Olga O.; Rohac, David J.; Erickson, Michael A.; Huffman, Kelly J. (Frontiers in Cell and Developmental Biology, 2022)
Background: Fetal alcohol spectrum disorders (FASD) represent a leading cause of non-genetic neuropathologies. Recent preclinical evidence from our laboratory suggests that prenatal ethanol exposure (PrEE), like other environmental exposures, may have a significant, transgenerational impact on the offspring of directly exposed animals, including altered neocortical development at birth and behavior in peri-pubescent mice. How these adverse behavioral outcomes are manifested within the brain at the time of behavioral disruption remains unknown. Methods: A transgenerational mouse model of FASD was used to generate up to a third filial generation of offspring to study. Using a multi-modal battery of behavioral assays, we assessed motor coordination/function, sensorimotor processing, risk-taking behavior, and depressive-like behavior in postnatal day (P) 20 pre-pubescent mice. Additionally, sensory neocortical area connectivity using dye tracing, neocortical gene expression using in situ RNA hybridization, and spine density analysis of spiny stellate cells in the somatosensory cortex using Golgi-Cox staining were examined in mice at P20. Results: We found that PrEE induces behavioral abnormalities including abnormal sensorimotor processing, increased risk-taking behavior, and increased depressive-like behaviors that extend to the F3 generation in 20-day old mice. Assessment of both somatosensory and visual cortical connectivity, as well as cortical RZRβ expression in pre-pubescent mice yielded no significant differences among any experimental generations. In contrast, only directly-exposed F1 mice displayed altered cortical expression of Id2 and decreased spine density among layer IV spiny stellate cells in somatosensory cortex at this pre-pubescent, post weaning age. Conclusions: Our results suggest that robust, clinically-relevant behavioral abnormalities are passed transgenerationally to the offspring of mice directly exposed to prenatal ethanol. Additionally, in contrast to our previous findings in the newborn PrEE mouse, a lack of transgenerational findings within the brain at this later age illuminates the critical need for future studies to attempt to discover the link between neurological function and the described behavioral changes. Overall, our study suggests that multi-generational effects of PrEE may have a substantial impact on human behavior as well as health and well-being and that these effects likely extend beyond early childhood.